The Role of the Business Press as an Information Intermediary - BUSHEE, BRIAN J.; CORE, JOHN E.; GUAY, WAYNE; HAMM, SOPHIA J.W. (Journal of Accounting Research, 2010)
ABSTRACT This paper investigates whether the business press serves as an information intermediary. The press potentially shapes firms' information environments by packaging and disseminating information, as well as by creating new information through journalism activities. We find that greater press coverage reduces information asymmetry (i.e., lower spreads and greater depth) around earnings announcements, with broad dissemination of information having a bigger impact than the quantity or quality of press‐generated information. These results are robust to controlling for firm‐initiated disclosures, market reactions to the announcement, and other information intermediaries. Our findings suggest that the press helps reduce information problems around earnings announcements.